Short video social media use and subjective wellbeing among young adults in rural China: The mediating roles of upward social comparison and online social capital - Yan Liu; Chen Wenling (Association for Scientific Computing Electrical and Engineering (ASCEE), 2023)
This paper aims to describe how videos affect human behavior, especially teenagers and other major human beings. Given the large number of young adults who use short video social media (e.g., TikTok, Douyin, and Kuaishou) in rural China, understanding how the use of such platforms affects their subjective wellbeing is crucial. This study examines the mediating roles of online social capital and upward social comparison in the relationships between short video social media use (intensity, active vs. passive use) and subjective wellbeing using data gathered from a web-based survey of 412 young adults living in rural China. Structural equation modeling demonstrated that active short video use is associated with a greater level of online social capital, which in turn is related positively to subjective wellbeing. Passive short video use is negatively associated with online social capital. Active short video use is also associated with a greater level of upward social comparison, whereas passive short video use is negatively associated with upward social comparison. Nevertheless, the relationship between upward social comparison and subjective wellbeing is not statistically significant. Use intensity was associated with neither online social capital nor upward social comparison. The findings extend the understanding of the psychologically powerful nature of short video social media platforms and their effects on subjective wellbeing among Chinese rural young adults.